Nurses’ Knowledge about MCH Services at Primary Health Care Centers in Rural Areas of Babylon Governorate - Iraq - Ibraheem Abdul-Hifid Hussein; Aysen Kamal Mohammed Noori (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: If you truly believe that every mother and every child deserve the best possible care, whetheror not the newborn comes into this world or during that time or after, that means that you are with us on thesame train. The study aims to assess nurses’ knowledge about MCH; and determine the relationship betweennurses’ knowledge and their demographic characteristics.Methods: A descriptive study was used to guide this study. The study included a convenience sample of(98) nurses.Data were collection using a self-report questionnaire. Data were analyzed using the statistical package forsocial science. The descriptive and inferential statistical measures were used.The study results revealed that nurses have a moderate knowledge. Nurses’ education, years of experience,and training courses significantly correlate with their knowledge.Conclusion : Nurses’ knowledge about maternal and childcare were moderate and their knowledge wereinfluenced by educational level, years of experience, and training. Longer years of experiences in maternaland childcare and more training on MCH program help to increase their knowledge.